The Development Impact of a Best Practice Seasonal Worker Policy - John Gibson; David McKenzie (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2010)
Seasonal migration programs are widely used around the world, and are increasingly seen as offering a potential "triple-win"- benefiting the migrant, sending country, and receiving country. Yet there is a dearth of rigorous evidence as to their development impact, and concerns about whether the time periods involved are too short to realize much in the way of benefits, and whether poorer, less skilled households actually get to participate in such programs. We study the development impacts of a recently introduced seasonal worker program which has been deemed to be "best practice". New Zealand's Recognised Seasonal Employer (RSE) program was launched in 2007 with an explicit focus on development in the Pacific alongside the aim of benefiting employers at home. A multi-year prospective evaluation allows us to measure the impact of participation in this program on households and communities in Tonga and Vanuatu. Using a matched difference-in-differences analysis based on detailed surveys fielded before, during, and after participation, we find that the RSE has indeed had largely positive development impacts. It has increased income and consumption of households, allowed households to purchase more durable goods, increased subjective standard of living, and had additional benefits at the community level. It also increased child schooling in Tonga. This should rank it among the most effective development policies evaluated to date. The policy was designed as a best practice example based on lessons elsewhere, and now should serve as a model for other countries to follow.
Keywords: O12; J61; F22; 330; Seasonal migration; Matched Difference-in-Differences